Seasonal variations and controlling factors of speleothem multi-proxy in southeastern China: Implications for the reconstruction of precipitation seasonality - Bao, Yanyan; Zhang, Haiwei; Niu, Xiaowen; Zhang, Rui; Lu, Jing; Meng, Binglin; Lu, Jiayu; Tan, Liangcheng; Cai, Yanjun; Cheng, Hai (Frontiers in Earth Science, 2023)
Precipitation in southeastern China exhibits strong seasonal variability, which significantly impacts local agricultural production and social development. However, the reconstruction of precipitation seasonality has been limited by the lack of precisely dated high-resolution paleoclimatic records. This study presents seasonal-scale multi-proxy records (trace elements: Mg/Ca, Sr/Ca Ba/Ca and stable isotopes: δ18O and δ13C) of a modern (1810-2009 AD) annually laminated stalagmite (EM1) from E’Mei Cave, Jiangxi Province in southeastern China. Comparative analysis of observation data with meteorological and simulation data shows that the seasonal variation of EM1 δ18O, derived from precipitation δ18O, is mainly controlled by the large-scale circulation and precipitation seasonality on an interannual timescale. The seasonal EM1δ18O variation is controlled by the seasonal precipitation δ18O, however, the most negative values of EM1 δ18O are higher than those of simulated calcite δ18O and the average amplitude of the seasonal variation of EM1 δ18O (~1.93‰) is much smaller than that of simulated calcite δ18O (~9.72‰) because of evaporation and the mixing of waters in the epikarst system. On the decadal timescales, variations of δ13C, Mg/Ca, Sr/Ca, and Ba/Ca were found to be strongly correlated, consistent with the variation of the local dry/flood index, indicating a common influencing factor of local hydroclimate change on a decadal timescale. However, their seasonal phase relationships vary between strong and weak summer monsoon conditions. We find a strong covariation between Mg/Ca and δ13C with Sr/Ca and Ba/Ca during the strong monsoon period (1951-1976), and they are in antiphase with seasonal δ18O variation. However, the seasonal variations of Sr/Ca and Ba/Ca transformed to dominantly antiphase with Mg/Ca and δ13C during the weak monsoon period (1977-1991 AD). Therefore, we suggest that Mg/Ca and δ13C are dominantly controlled by the local hydroclimate changes on seasonal timescales but Sr/Ca and Ba/Ca might have been affected by complex processes in the epikarst under different hydrothermal configuration conditions. The findings indicate the potential of the variation of the seasonal phase relationships between multi-proxy records in reconstructing precipitation seasonality changes under different hydrothermal backgrounds.